Voices of protest in selected poems of cecils Rajendra and Fan Yew Teng - Mohammad Sidik Ariffin (Tanjong Malim, 2004)
Voices of protest in selected poems of cecils Rajendra and Fan Yew Teng by Mohammad Sidik Ariffin